Desain Solusi Otomasi Dan Energi Terbarukan Peternakan Ayam Pintar di Sukadana Lampung Timur - Muhammad Ferdiansyah; Lika Mariya; Agus Salim Wardana (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This research aims to design and test an efficient and sustainable renewable energy-based automation system for poultry farm operations in rural areas such as Sukadana, East Lampung. The system utilizes solar panels as the primary energy source integrated with automation components, including a humidity control fan, heating sensor, submersible water supply pump, and booster pump for the drinking system. Research steps include a literature review, field needs analysis, prototype design and development, and laboratory testing. Results indicate that the system maintains coop temperatures within the optimal range of 29–34°C and humidity at 50–55%, while reducing energy consumption by up to 43% compared to conventional systems reliant on PLN electricity. These findings underscore the potential of solar panels in areas with high sunlight intensity and demonstrate that integrating IoT with renewable energy can reduce dependency on conventional electricity and lower long-term operational costs. Implementing renewable energy-based automation solutions can benefit farms with limited energy access, enhancing efficiency and sustainability. Development recommendations include increasing energy storage capacity and strengthening IoT-based monitoring systems to optimize performance under diverse weather conditions.